Building blocks of the universe - Asimov, Isaac, 1920-1992. (London, New York, Abelard-Schuman, 1961)
A brief discussion of 102 basic chemical elements introduces a more detailed account of the structure, forms, and uses of the most common elements.
Includes index.
Keywords: Chemical elements -- Juvenile literature; Chemical elements